Analisis Mutu Pelayanan Klinis Kasus Asma Bronkial Anak di Unit Gawat Darurat Rumah Sakit - Rahmaniar, Shabrina Ari; Rosa, Elsye Maria (Universitas Ahmad Dahlan, 2017)
Background: Bronchial asthma is one of the top 10 common diseases in children in the emergency room navy hospital dr. Azhar Zahir Manokwari West Papua in the past one year. Asthma bronchial requiring therapeutic measures quickly and efficiently to improve the quality of patient care in the emergency room. Medical audit was strongly associated with improved quality and standardization for the excellent medical services in hospitals, therefore any health care providers are required to provide good service to do a medical audit. This study is to evaluate the quality of medical services asthma bronchial cases of Children in the Emergency room for the excellent medical services at Navy Hospital dr. Azhar Zahir Manokwari West Papua. Method: This study is a quantitative descriptive study, were taken in a non-probability sampling with consecutive sampling method. Criteria for sample: patients who have been diagnosed with asthma bronchial, aged one to 14 years. Result: Most patients with asthma bronchial in the emergency room was mild attacks category. The application of medical standards asthma bronchial cases in these hospitals were not good enough. It was seen from the results of the analysis, where there were some standard actions that are not performed by a doctor, among others: observation for two hours, the line installation parenteral, clinical check after 12 hours, and thoracic radiograph. Conclusion: The quality of medical care to patients who did not conform to the standard treatment of bronchial asthma in children because there were some actions that are not limited facilities and infrastructure in the emergency room.